Ringmaster : Vince McMahon and the unmaking of America - Riesman, Abraham (Atria Books, 2023)
Featuring never-before-seen research and exclusive interviews with people who witnessed, aided, and suffered from his ascent, this unauthorized investigative chronicle of the media mogul, defining cultural force, and one of Donald Trump's closest friends uses his story as a new lens for understanding contemporary America.